(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Annotation:” movement is so important that with its influence it can replace any factors, but not all the healing factors of the world can compensate for movement, " wrote Torquato Tasso, a famous Italian poet. The concept of a healthy lifestyle deeply covers the maturation of human behavior and physical maturation, and all aspects of this life. The main content of a person’s self-knowledge is highlighted, such as compliance with sanitary and hygienic rules and requirements, being complimentary to those around him, being able to control his own psychic States, eating right, physical education and sports, giving up harmful habits.